2005
DOI: 10.1002/qsar.200540009
|View full text |Cite
|
Sign up to set email alerts
|

Using Catalyst-Substrate Coimmobilization for the Discovery of Catalysts for Asymmetric Aldol Reactions in Split-and-Mix Libraries

Abstract: "Catalyst -substrate coimmobilization" has been used for the discovery of highly active and selective peptidic catalysts for asymmetric aldol reactions within split-and-mix libraries. This screening method is based on the coimmobilization of one reaction partner along with each library member via a bifunctional linker on the library beads followed by mixing of this library with a labeled second reaction partner. Here we discuss the details of the combinatorial screening and demonstrate that the exchange of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
(14 reference statements)
1
14
0
Order By: Relevance
“…H-Pro-Pro-b-Asp-NH 2 4 has an additional methylene group in the spacer to the C-terminal amide, whereas in its analogue H-Pro-Pro-b-AspScheme 1. a) Aldol reactions catalyzed by H-Pro-Pro-Asp-NH 2 1 and b) lowest energy structure of 1 as predicted by calculations using MacroModel 8.0. [10] Scheme 2. Peptides 2-7 closely related to the asymmetric catalyst 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…H-Pro-Pro-b-Asp-NH 2 4 has an additional methylene group in the spacer to the C-terminal amide, whereas in its analogue H-Pro-Pro-b-AspScheme 1. a) Aldol reactions catalyzed by H-Pro-Pro-Asp-NH 2 1 and b) lowest energy structure of 1 as predicted by calculations using MacroModel 8.0. [10] Scheme 2. Peptides 2-7 closely related to the asymmetric catalyst 1.…”
Section: Resultsmentioning
confidence: 99%
“…[1,7,8] Using the method of "catalyst-substrate coimmobilization" which allows identification of catalysts within splitand-mix libraries, [9] we discovered the peptides HPro-Pro-Asp-NH 2 and H-Pro-d-Ala-d-Asp-NH 2 as catalysts for asymmetric aldol reactions. [10] Both peptides emerged as consensus sequences from the screening of 3375 different tripeptides for catalytic activity. Subsequent solution-phase experiments revealed that in particular H-Pro-Pro-Asp-NH 2 1, is a highly active and selective catalyst: 1 mol% of 1 suffices to catalyze aldol reactions between acetone and several aldehydes with good to excellent yields and enantioselectivities (Scheme 1 a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the introduction of a proline-catalyzed asymmetric aldol reaction of aldehydes reported by List et al [19], prolinamide catalysts for this reaction have been actively developed [20,21]. Synthetic peptides in prolinamide catalysts, are recognized as effective catalysts for the direct asymmetric aldol reaction using aldehydes as electrophiles [22][23][24][25][26][27][28][29][30][31][32][33]. However, peptide catalysts for the direct asymmetric aldol reaction using ketones as electrophiles are limited [29,[33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%